A review of the classification of rabies virus lineages maintained by insectivorous bats in Brazil - Oliveira, R. N.; Castilho, J. G.; Batista, H. B. C. R.; Paula, F. C.; Carnieli Jr, P.; Lima, J. Y. O.; Macedo, C. I.; Menozzi, B. D.; Carrieri, M. L.; Kotait, I.; Miranda, C. C. P.; Brandão, P. E. (Revista de Educação Continuada em Medicina Veterinária e Zootecnia do CRMV-SP, 2013)
Little was known about the importance of nonhematophagous bats in the epidemiology of rabies in Brazil and most of Latin America until the 1980s. From that decade on, as canine rabies came under control in many municipalities and molecular and antigenic typing was incorporated in surveillance programs, the importance of nonhematophagous bats in the epidemiology of the disease began to be appreciated in these countries. In Brazil, genetic studies based on gene N have shown that different lineages are circulating in insectivorous bats from the species Tadarida brasiliensis, Nyctinomops laticaudatus and genus Myotis, Eptesicus, Molossus, Histiotus and Lasiurus. In most studies, the characterization of these lineages is based on only 264 nt of the carboxyterminal region of the viral nucleoprotein, when the ideal would be to use the complete N gene. The aims of the present study was to review the genetic classification of the RABV isolated from insectivorous bats from Brazil based on current literature, Genbank dataset and new partial DNA sequencing of the nucleoprotein comparing the phylogenetic analysis of N gene based on 1218 nucleotides (nt 203 to nt 1420) with that based on 264 nucleotides (nt 1157 to nt 1420), corresponding respectively to amino acids 45 to 450 and 363 to 450 of the viral nucleoprotein. Phylogenetic analysis demonstrated the existence of at least eleven lineages of RABV associated with different genera and species of insectivorous bats. Nine of these lineages have already been described in literature while two of them were herein characterized for the first time and associated to the genus Myotis and Lasiurus. There were no differences in the classification of Brazilian strains by comparing the two alignments used, but changes were observed in phylogenetic relationships between the clusters, with bootstrap values always greater regarding the 1218 nt tree. Two sequences of RABV from the genus Myotis from Uruguay and Chile did not keep the same classification after the analyses with the two alignment lengths. These findings should be taken into account in molecular epidemiology of rabies, as sources of infections might be determined in a more accurate way and also in the correct use of fragments of the N Gene for the classification of lineages of RABV.